Desenvolvimento sustentável na cafeicultura da região de Patrocínio-MG: uma visão sobre a certificação em propriedades - Marques, Adriana Souza (2022)
Brazil is the largest coffee producer in the world, and its exploitation has brought with it many foreign exchange and some damage to the environment. The culture occupies a large territorial area in several Brazilian states, such as São Paulo, Minas Gerais, Paraná, Bahia and Espírito Santo. With the increase in global environmental concern, Brazilian coffee growers have also increased care with production sustainability and environmental preservation, contributing to the reduction of damage to the environment. With the awakening of ecological awareness, it becomes necessary to adopt procedures that are less aggressive to the environment, and the use of good management practices in agriculture. Sustainable agriculture must be promoted and little by little they have guaranteed space in national production and developing an ecological awareness in consumers and throughout the production chain. Coffee growing is part of a complex culture, which develops with different patterns, employing only family labor, as formal and informal salaried employees, and different technological levels. With this, the available certification programs appear as an option to improve the management system, contributing to the implementation and development of production in a more sustainable way, but audits can represent a high cost/benefit for producers. This study aimed to evaluate aspects of certification programs as a management tool, and the benefits and difficulties of accessing certification. The work was developed in the region of Patrocínio-MG, known for the high production of quality coffee in the Cerrado region, and with properties with the use of technologies characterized among family members, of medium and large size. For the diagnosis of the properties, a certified farm within Patrocínio was determined as a reference, visited and characterized according to a compliance form and the other producers were asked to participate by answering a structured questionnaire linked to the questions of obtaining certification. in the different programs available in the coffee market. The answers were tabulated in percentile graphs and had their content analyzed in a critical analytical way and discussed based on other works already carried out in the same line of research. With this, it is concluded that the certification process can be a great ally for coffee producers in improving sustainable management and quality coffee production, but it still needs to be better disseminated among coffee growers, demystifying the idea of bureaucratization.